Hard and Soft Sciences: How Both Fields Differ in Presenting Research Gaps - Ade Hidayat; Safnil Safnil; Arono Arono (Postgraduate, University of Mataram, 2023)
Studies on research gap presentation only focused on certain field of studies, whereas there are no studies that try to compare different field of studies. Therefore, this research aims to fill the gap and investigate how authors from different field of studies present research gap in their research articles. As the research gap presentation are mainly occurred in the beginning sections of an article, 100 article introductions from 10 journals have been analyzed. The journals were divided into two major fields which are Hard Science and Soft Science. Analysis was done to find out what types of research gap strategies that is used by the authors following the seven research gaps framework: evidence gap, knowledge gap, practical-knowledge gap, methodological gap, empirical gap, theoretical gap, and population gap. The results show that authors from both Hard Sciences and Soft Science used knowledge gap as the most frequently used strategy and theoretical gap as the least frequently used strategy. Other result is authors in Hard Sciences use more varied strategies than in Soft Science. Furthermore, both fields seem quite similar regarding the occurrence of research gaps while still has differences in some parts.